Development policies of Central and Eastern European states : from aid recipients to aid donors - Horky-Hluchan, Ondrej, 1980-; Lightfoot, Simon (London : Routledge, 2013)
This text explores whether the development cooperation programmes of the majority of CEESs reflect the so-called'transition experience' of moving from authoritarianism and socialism to democracy and modern liberalism. It also explores the extent to which these donors are aligned with the approaches of the DAC donors.
Includes bibliographical references and index.
Keywords: Economic assistance -- Europe, Central; Economic assistance -- Europe, Eastern; Europe, Central -- Economic policy -- 1989-; Europe, Eastern -- Economic policy -- 1989-